What is the best initial treatment for plantar warts in children?. Issue 12 (December 2015) - Elsaid, Saleh; Alvarez, Erik; Jabeen, Sameera; Jamal, Naiomi; Howrey, Bret
Abstract : Evidence‐Based Answer : Topical salicylic acid likely works better than placebo for the treatment of plantar warts in patients of all ages, while cryotherapy may be no better than placebo (SOR: B, meta‐analysis with logically inconsistent outcomes). Cantharidin‐podophyllotoxin‐salicylic (CPS) acid is perhaps more effective than cryotherapy for the treatment of plantar warts in children (SOR: C, small RCT). Intralesional Candida albicans injection is no better than other modalities for the treatment of plantar warts in all age groups (SOR: C, nonrandomized comparison study).